Cover Image, Volume 1448, Issue 1. Issue 1 (24th July 2019) - Li, Zhongqiang; Zaid, Waleed; Hartzler, Thomas; Ramos, Alexandra; Osborn, Michelle L.; Li, Yanping; Yao, Shaomian; Xu, Jian
Abstract : On the back cover : From Zhongqiang Li et al ., "Indocyanine green‐assisted dental imaging in the first and second near‐infrared windows as compared with X‐ray imaging."https://doi.org/10.1111/nyas.14086 .